Transformasi Rasa Bunga Telang: Penerapan Diversifikasi Produk Pangan sebagai Ide Bisnis Rumahan bagi Mahasiswa - Bahauddin Alqostolani; Cindy Dwi Cahyani; Medya Ayunda Fitri; Zahrotul Azizah; Ahmad Musonnifin Aziz; Listin Fitrianah; Luqman Hakim; Muhammad Mansur Yafi; Muchammad Tamtiz; Alifah Dian Rahmania; Trisna Kumala Dhaniswara (Universitas Nahdlatul Ulama Sidoarjo, 2025)
Indonesia has a wealth of flora with great potential to be developed as a functional food ingredient with economic value. One local plant that has this potential is the butterfly pea flower (Clitoria ternatea), which is known for its attractive natural color and beneficial bioactive compounds. This community service activity aims to introduce diversified butterfly pea flower processing to students through training in making food products as a home business idea based on local potential. The training was carried out using the method of material presentation, interactive discussions, and organoleptic product testing. The products developed include Azure Petal Tea, Citrus Spice Infusion, Blue Velvet Milk Tea, and Indigo Dream Pudding. The processing process is carried out using simple methods that are easy to apply. The results of the activity showed that participants were highly enthusiastic about the process of creating product characteristics and demonstrated a better understanding of the potential for diversifying butterfly pea flowers into value-added food products.